Activation-induced layered structure in NiCoAl by atomic modulation for energy storage application. (January 2023) - Kumaravelu, T.A.; Ramakrishnan, A.; Lu, Y.R.; Chen, J.L.; Chen, S.W.; Du, C.H.; Chen, M.Y.; Yeh, P.H.; Kandasami, A.; Chen, C.H.; Dong, C.L.
Abstract: The surface activation of alloys favors their electrochemical interactions, ion diffusivity, and the rapid kinetics of ions and electrons, leading to the formation of self-supported layered double hydroxides (LDHs) in them. However, the formation of LDHs at different depths in the alloy upon activation, their electronic/atomic structures, and their electrochemical charge storage mechanism, have not been thoroughly explored. Herein, Ni ion-substituted CoAl alloys are prepared by arc melting and activated by KOH electrolyte, which is responsible for the modulation of the atomic configuration as confirmed by XRD. Raman depth mapping demonstrates how the LDHs vary with depth upon activation and that the octahedral and tetrahedral symmetry sites of CoO and Co3 O4 are responsible for the formation of the layered structures of CoOOH and Co(OH)2, respectively. The activated Ni10 Co85 Al5 has a superior volumetric capacitance of 4.15 F/cm 3 at 0.5 mA/g, which is 38.6 times that of an unactivated one, and excellent cyclic stability up to 5000 cycles, and a voltage of 0.54 V generated from a fabricated supercapacitor cell. X-ray Absorption Spectroscopy (XAS) analysis indicates greater charge transfer by Co than by Ni and the modulation of the local atomic structures facilitates electrochemical charge storage in Ni10 Co85 Al5 . This work presents an easy route for the development of advanced LDHs, and the mechanism of electrochemical charge storage in them. Highlights: This is the first report on free-standing LDHs in NiCoAl-alloy by activation. Raman depth mapping reveals layered double CoOOH and Co(OH)2 in Ni10 Co85 Al5 -A. XAS unravels greater charge transfer by Co than by Ni, and the reduction of Co–Co. The volumetric capacitance of activated Ni10 Co85 Al5 is 38.6 times that of Co95 Al5 -A.